Primary immunization of meningococcal meningitis vaccine among children in Hangzhou, China, 2008–2017 - Xinren Che; Yan Liu; Jun Wang; Yuyang Xu; Xuechao Zhang; Wenwen Gu; Wei Jiang; Jian Du; Xiaoping Zhang (Human Vaccines & Immunotherapeutics, 2021)
Background Although China’s Expanded Program on Immunization (EPI) provides two doses of group A meningococcal polysaccharide vaccine (MPV-A) for children younger than 2 y, more self-paying group A and group C meningococcal polysaccharide conjugate vaccine (MCV-AC) has been used as an alternative to MPV-A, to prevent Neisseria meningitidis serogroup C (Men-C) earlier. We evaluated the pattern of MPV-A and MCV-AC utilization to provide evidence for China to upgrade the national meningococcal meningitis vaccination strategy. Methods Children born between 2008 and 2017 registered in Hangzhou’s Immunization Information System (HZIIS) were included. Descriptive epidemiological methods were used to characterize the data. Adverse event following immunization (AEFI) was collected from Chinese national adverse event following immunization information system (CNAEFIIS) to compare the safety of MPV-A and MCV-AC. Results Data of 1149,027 children from HZIIS were analyzed. The average immunization rate of meningococcal meningitis vaccine (MenV) was 97.50%. Percentages of children using MPV-A-only, MCV-AC-only, and MPV-A/MCV-AC sequential schedules were 68.20%, 29.73%, and 2.07%, respectively. The vaccination rate of MCV-AC-only increased by age and it was higher in resident children than migration children. The incidence rate of AEFI of MPV-A and MCV-AC was 53.36 per 100,000 and 62.13 per 100,000, respectively. Conclusion Children in Hangzhou had high MenV coverage. MCV-AC-only schedule use increased by year and was higher in urban areas among locally born children. Both MPV-A and MCV-AC were safe for children, while MCV-AC could protect against Men-C more effectively. This supports the rationale to introduce MCV-AC into China’s EPI system for free instead of MPV-A.